ANALISIS NILAI TUKAR NELAYAN (NTN) MASYARAKAT NELAYAN DI KAMPUNG TANJUNG BATU KECAMATAN PULAU DERAWAN KABUPATEN BERAU - Suryaningsih; Erwiantono; Oon Darmansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2018)
Tanjung Batu Village was coastal area which had very big fisheries potency that was utilized by the fishermen society. Natural resources and and social economic condition which has changed giving effect to fisherman society prosperity. This research aim was to analze prosperity level based on indicator of Fisherman Exchange Value (Nilai Tukar Nelayan/NTN) and to identify the fisherman society saving behavior on Tanjung Batu Village Derawan Island Sub-District Berau Regency. This research was conducted on September 2017 to June 2018 in the Tanjung Batu Village, Pulau Derawan Sub-District, Berau Regency. Research was used the case study method and applied purposive sampling to select 50 respondents based on six dominant fishing gear which were usually used. Data were analyzed by qualitative-quantitative descriptive method that focused on Fisherman Exchange Value (Nilai Tukar Nelayan /NTN), Index of Fisherman Exchange Value (Indeks Nilai Tukar Nelayan/INTN) and the fishermen society saving behavior. NTN analysis result showed that NTN value of fisherman family in 2016 and 2017 was still above one but decreased. INTN analysis result of fisherman family in 2016 and 2017 was under 100% and decreased. Fisherman Family on Tanjung Batu Village had financial surplus and saving potency based on the NTN value.